Heat Transfer Study of Helically Coiled Tube Heat Exchanger - Yusni, Alif Aiman (IRC, 2016)
Improving heat transfer is one of the main focuses in the energy field. Along with that, helically coiled heat exchangers has been introduced since decades ago. As it offers high heat transfer performance and has geometry compactness, helically coiled heat exchanger has been widely utilized in industrial applications. They are commonly employed in power plant, nuclear reactor, refrigeration system etc. This present work is aiming to investigate the performance of different cross- section geometry and configuration (eccentricity) of tube- in- tube helical type heat exchanger. The numerical study was conducted by using CATIA V5 for models development and ANSYS Fluent 16.2 CFD software.